2014
DOI: 10.1038/ejcn.2014.140
|View full text |Cite
|
Sign up to set email alerts
|

The influence of socioeconomic factors and family context on energy-dense food consumption among 2-year-old children

Abstract: High socioeconomic characteristics were associated with lower consumption of energy-dense food by 2-year-old children, mainly soft drinks and sweets. This influence is not only from parents' background but also from the preceding generations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 33 publications
(36 reference statements)
7
35
0
1
Order By: Relevance
“…Findings of this study are consistent with other studies which have investigated the determinants of dietary behaviors of infants and toddlers and have found that children of younger mothers had less healthy diets than those of older mothers [41,43,[51][52][53][54][55][56]. We did not however, find an independent association with discretionary food intake and maternal education reported in other studies [41,51,[53][54][55][56].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Findings of this study are consistent with other studies which have investigated the determinants of dietary behaviors of infants and toddlers and have found that children of younger mothers had less healthy diets than those of older mothers [41,43,[51][52][53][54][55][56]. We did not however, find an independent association with discretionary food intake and maternal education reported in other studies [41,51,[53][54][55][56].…”
Section: Discussionsupporting
confidence: 91%
“…Our finding that first born children consumed less of their total energy from discretionary foods than did children with two or more older siblings is consistent with other Australian [18,58] and international [41,[54][55][56] studies which have reported poorer diet quality and dietary patterns among higher birth order children. It has been postulated that older children in the family who are exposed to these foods outside of the home and through advertising may pester their parents for these foods [18], thus increasing the availability of these foods in the household.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result was unexpected, as previous analyses on this dataset revealed that higher educated mothers showed more health‐conscious snack giving behaviour compared with lower educated mothers (Damen, Luning, et al, ). Moreover, others (Bargiota, Delizona, Tsitouras, & Koukoulis, ; Durão et al, ; Emmett & Jones, ; Gevers et al, ; Saldiva et al, ; van Ansem, van Lenthe, Schrijvers, Rodenburg, & van de Mheen, ; Vilela et al, ) also found higher educated mothers to be more health‐conscious compared with lower educated mothers. Because most value conflicts in the current study are health related, it was expected that when mothers were more health‐conscious, they would also experience value conflicts more often.…”
Section: Discussionmentioning
confidence: 97%
“…There is strong evidence indicating that socioeconomic and demographic characteristics (such as maternal age and education, household income, children having older siblings) 14,15 and family life habits (such as parent nutrition knowledge and food parenting practices) play an important role in children's food preferences 16,17,18 .…”
Section: Introductionmentioning
confidence: 99%